Depletion of high-mobility group box 2 causes seminiferous tubule atrophy via aberrant expression of androgen and estrogen receptors in mouse testis. Issue 6 (7th October 2021) - Sugita, Naohiro; Choijookhuu, Narantsog; Yano, Koichi; Lee, Deokcheol; Ikenoue, Makoto; Fidya,; Taniguchi, Noboru; Chosa, Etsuo; Hishikawa, Yoshitaka
Abstract: High-mobility group box 2, a chromatin-associated protein that interacts with deoxyribonucleic acid, is implicated in multiple biological processes, including gene transcription, replication, and repair. High-mobility group box 2 is expressed in several tissues, including the testis; however, its functional role is largely unknown. Here, we elucidated the role of high-mobility group box 2 in spermatogenesis. Paraffin-embedded testicular tissues were obtained from 8-week-old and 1-year-old wild-type and knock-out mice. Testis weight and number of seminiferous tubules were decreased, whereas atrophic tubules were increased in high-mobility group box 2-depleted mice. Immunohistochemistry revealed that atrophic tubules contained Sertoli cells, but not germ cells. Moreover, decreased cell proliferation and increased apoptosis were demonstrated in high-mobility group box 2-depleted mouse testis. To elucidate the cause of tubule atrophy, we examined the expression of androgen and estrogen receptors, and the results indicated aberrant expression of androgen receptor and estrogen receptor alpha in Sertoli and Leydig cells. Southwestern histochemistry detected decreased estrogen response element–binding sites in high-mobility group box 2-depleted mouse testis. High-mobility group box 1, which has highly similar structure and function as high-mobility group box 2, was examined by immunohistochemistry and western blotting, which indicated increased expression in testis. These findings indicate a compensatory increase in high-mobility group box 1 expression in high-mobility group box 2 knock-out mouse testis. In summary, depletion of high-mobility group box 2 induced aberrant expression of androgen receptor and estrogen receptor alpha, leading to decreased germ cell proliferation and increased apoptosis which resulted in focal seminiferous tubule atrophy. Abstract : Depletion of High-mobility group box 2 induced aberrant androgen receptor and estrogen receptor alpha expression, leading to decreased germ cell proliferation and increased apoptosis, resulting in seminiferous tubule atrophy. Graphical Abstract: